A review of HLA and COVID-19 association studies - Žunec, Renata (Array, 2020)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is reported to vary across different populations in the prevalence of infection, in the death rate of patients, in the severity of symptoms and in the drug response of patients. Among host genetic factors that can influence all these attributes human leukocyte antigen (HLA) genetic system stands out as one of the leading candidates. Case-control studies, large-scale population-based studies, as well as experimental bioinformatics studies are of utmost importance to confirm HLA susceptibility spectrum of COVID-19. This review presents the results of the first case-control and epidemiological studies performed in several populations, early after the pandemic breakout. The results are pointing to several susceptible and protective HLA alleles and haplotypes associations with COVID-19, some of which might be of interest for the future studies in Croatia, due to its common presence in the population. However, further multiple investigations from around the world, as numerous as possible, are needed to confirm or deteriorate these preliminary results.